3p+6+4=10

Simple and best practice solution for 3p+6+4=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p+6+4=10 equation:


Simplifying
3p + 6 + 4 = 10

Reorder the terms:
6 + 4 + 3p = 10

Combine like terms: 6 + 4 = 10
10 + 3p = 10

Add '-10' to each side of the equation.
10 + -10 + 3p = 10 + -10

Combine like terms: 10 + -10 = 0
0 + 3p = 10 + -10
3p = 10 + -10

Combine like terms: 10 + -10 = 0
3p = 0

Solving
3p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Divide each side by '3'.
p = 0

Simplifying
p = 0

See similar equations:

| 216=8x+64 | | f=8484(578755)4736/245 | | 5n-28=+10n+12 | | -3v-10=v+6 | | 3x=12x-9 | | -32-8x=-8(1+4x) | | 49v^2+42v+9=0 | | -49-3p=-4-12p | | 3x=12x-2 | | cos(x)-sin(x)=1 | | -10=p-12 | | 10=3u-11 | | -24-x=5x-9x-9 | | p+8=-2 | | 4p^2+9p-9=0 | | 9x-5x=-20 | | b+4=23 | | x-17=-28 | | -2=v-8 | | -12+x=-17 | | 7x+14y=122 | | -9=r-16 | | 6p^2-13p+7=0 | | -x^2-40x-76=0 | | 26=x+17 | | -2-5(1-4)=127 | | 14=-4+n | | 3(2+v)= | | 18=6-3-3 | | -4x-6=12y | | 4(x)+2(23-x)=62 | | k-20=-40 |

Equations solver categories